2015
DOI: 10.1002/adsc.201500638
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to the Efficient Syntheses of Chiral Phosphino‐ Carboxylic Acid Esters

Abstract: Thec atalytic hydrophosphination reaction is one of the most sustainablec hemical transformations today.H ere,t he palladium-catalyzed asymmetric P À Ha ddition of diarylphosphines with N-enoylbenzotriazoles and analogues is described. Chiral phosphinep roductsa re obtained in 100%a tom economy and without cumbersome protection-deprotection manipulations.T he obtained productsc an be subsequently transformedt ob ear various functionalities,i ncluding phosphino-carboxylic esters which play critical roles in cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Racemic secondary phosphines were also tolerated well, providing the corresponding tertiary phosphines with two chiral centers in high yields with reasonable enantiocontrol (up to 82% ee and 91:9 dr). Later, the application of this methodology was extended to the asymmetric hydrophosphination of dienones, yielding chiral bis-phosphines or tertiary P-heterocycles with excellent stereoselectivities (up to 99:1 dr and 99% ee; Scheme a). , Later studies showed that a range of α,β-unsaturated substituted alkenylisoxazoles, esters, and amides were suitable substrates for this reaction. Most recently, the authors successfully developed a ( S )- 124a –Pd-promoted ACA of diphenylphosphine to ferrocenyl enones, which provided an efficient route to valuable chiral ferrocenyl phosphapalladacycle catalysts (Scheme b) . It is noteworthy that the substituent on the double bond of the ferrocenyl enones greatly affected the reactivity.…”
Section: C–heteroatom Bond Formation By Metal-catalyzed Aca Reactionsmentioning
confidence: 99%
“…Racemic secondary phosphines were also tolerated well, providing the corresponding tertiary phosphines with two chiral centers in high yields with reasonable enantiocontrol (up to 82% ee and 91:9 dr). Later, the application of this methodology was extended to the asymmetric hydrophosphination of dienones, yielding chiral bis-phosphines or tertiary P-heterocycles with excellent stereoselectivities (up to 99:1 dr and 99% ee; Scheme a). , Later studies showed that a range of α,β-unsaturated substituted alkenylisoxazoles, esters, and amides were suitable substrates for this reaction. Most recently, the authors successfully developed a ( S )- 124a –Pd-promoted ACA of diphenylphosphine to ferrocenyl enones, which provided an efficient route to valuable chiral ferrocenyl phosphapalladacycle catalysts (Scheme b) . It is noteworthy that the substituent on the double bond of the ferrocenyl enones greatly affected the reactivity.…”
Section: C–heteroatom Bond Formation By Metal-catalyzed Aca Reactionsmentioning
confidence: 99%
“…The absolute configuration of 3ba was determined to be R by comparing its optical rotation value with reported data. 6g The stereochemistry in other products was tentatively assigned by structural analogy.…”
Section: Table 1 Optimization Of the Reaction Condition...mentioning
confidence: 99%
“…The prepared products could be further transformed into phosphine-carboxylic esters via a one-pot protocol with almost no loss in enantiomeric excess (Scheme 10). 24 One of the products prepared by this methodology was used to prepare a gold complex that showed tumor suppression potential.…”
Section: Scheme 9 Enantiodivergent Hydrophosphination Of 4-oxo-enamidesmentioning
confidence: 99%